2008
DOI: 10.1007/s11606-008-0839-y
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Judgment

Abstract: To the Editor: Drs. Torke, Alexander, and Lantos have clearly and succinctly summarized the vast literature on the substituted judgment approach to surrogate decision-making. 1 This approach targets the exact decision the incapacitated patient would make under the circumstances. The authors point out that, despite the strong philosophical and psychological appeal of substituted judgment, considerable empirical evidence questions its feasibility. They then suggest two alternative approaches for making health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This suggests that EA men may be more family focused than ME men and is consistent with the prevalence of familism in East Asia, 16,17,36 studies showing a stronger familism orientation in Christian/Philippines-educated than Muslim/ Saudi Arabia-educated respondents in relation to organ donation, 29 and studies showing culture dependency of end-of-life preferences. 21,22,37 However, although Q-methodology identified relatively familism-influenced models in all EA viewpoints, there were also a relatively familism-influenced model in the ME S-viewpoint and a relatively family burden-influenced model in the ME Pviewpoint. Furthermore, there were a relatively family non-financial burden-uninfluenced model and a relatively family financial needs-uninfluenced model in the EA N-viewpoint, demonstrating a clear overlap between the 2 cultures.…”
Section: Comparing Middle Eastern and East Asian Menmentioning
confidence: 88%
“…This suggests that EA men may be more family focused than ME men and is consistent with the prevalence of familism in East Asia, 16,17,36 studies showing a stronger familism orientation in Christian/Philippines-educated than Muslim/ Saudi Arabia-educated respondents in relation to organ donation, 29 and studies showing culture dependency of end-of-life preferences. 21,22,37 However, although Q-methodology identified relatively familism-influenced models in all EA viewpoints, there were also a relatively familism-influenced model in the ME S-viewpoint and a relatively family burden-influenced model in the ME Pviewpoint. Furthermore, there were a relatively family non-financial burden-uninfluenced model and a relatively family financial needs-uninfluenced model in the EA N-viewpoint, demonstrating a clear overlap between the 2 cultures.…”
Section: Comparing Middle Eastern and East Asian Menmentioning
confidence: 88%
“…For example, ability to self-care was the most important and burden on family was the third most important end-of-life issues for patients, whereas amount of pain was the most important issue and burden on family was not an important issue for surrogates [41]. A study on advance care planning showed that men focused on minimally acceptable functional capacities while women took a broader view including meaningful times and places to die and psychological and economic burdens on families [42]. Another study showed that age, religiosity, and liberal-conservative social outlook explained 8, 5, and 5% of the variance in physicians attitude toward end-of-life decision-making [43].…”
Section: Discussionmentioning
confidence: 99%
“…End-of-life preferences may be culture and sex [21,22,43] as well as religiosity [23] dependent. We observed two notable differences between ME and EA respondents.…”
Section: Differences Between Me To Ea Respondentsmentioning
confidence: 99%